Exploring the potential of gemcitabine-metal–organic frameworks in combating pancreatic cancer under ketogenic conditions - Samira Nekoufar; Marjan Ghorbani; Sahar Safaei; Gholamreza Alinezhadi Khosroushahi; Farzad Izak Shirian; Behzad Baradaran; Masoumeh Tavakoli-Yaraki (BMC Cancer)
Abstract Background Inadequate treatment responses, chemotherapy resistance, significant heterogeneity, and lengthy treatment durations create an urgent need for new pancreatic cancer therapies. This study aims to investigate the effectiveness of gemcitabine-loaded nanoparticles enclosed in an organo-metallic framework under ketogenic conditions in inhibiting the growth of MIA-PaCa-2 cells. Methods Gemcitabine was encapsulated in Metal–organic frameworks (MOFs) and its morphology and size distribution were examined using transmission electron microscopy (TEM) and Dynamic light scattering (DLS) with further characterization including FTIR analysis. Various drug groups were established to evaluate their influences on cell cytotoxicity, apoptosis rate, cell cycle distribution, levels of superoxide dismutase (SOD), glutathione peroxidase (GPx), malondialdehyde (MDA), and cell migration. Results The gemcitabine-MOF was thoroughly analyzed to determine its size, morphology, and chemical composition, confirming its successful preparation. The treatment results showed an increase in the number of apoptotic cells following gemcitabine-MOF treatment, which was found to be associated with cell cycle arrest in the sub-G1 phase. Moreover, these treatments also resulted in reduced cell migration, decreased activity of antioxidant enzymes (SOD, GPx), and increased accumulation of MDA. Additionally, when exposed to ketogenic conditions (where beta-hydroxybutyrate is present in a glucose-limited medium), there was a further increase in cell cycle arrest, accompanied by a more pronounced decrease in SOD and GPx activity, as well as decreased migration. Conclusion The use of metal–organic framework to encapsulate gemcitabine yielded notable pro-apoptotic effects in MIA-PaCa-2 cells with which ketogenic conditions had a synergistic effect that can hold promise for improving therapeutic options. Graphical Abstract